THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND COMPLIANCE WITH MEDICATION IN PULMONARY TB PATIENTS IN THE WORKING AREA OF THE BOJONEGORO PUBLIC HEALTH CENTER BASED ON LAWRENCE W. GREEN'S THEORY - Avrinda Debora Sinda Mercelin; Evita Muslima Isnanda Putri; Ahmad Maftukhin; Titik Nuryanti; Rahmawati (PT. Radja Intercontinental Publishing, 2026)
Pulmonary tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis and requires long-term treatment for six months. Non-compliance with medication is one of the main causes of therapy failure and increases the risk of Multi Drug Resistance (MDR). Family support is an important factor in improving medication compliance in pulmonary TB patients. This study aims to analyze the relationship between family support and medication compliance in pulmonary TB patients in the Bojonegoro Community Health Center working area based on Lawrence W. Green's theory. This study used a quantitative correlational design with a cross-sectional approach. The study sample was 36 pulmonary TB patients who had undergone treatment for six months using a total sampling technique. The independent variable was family support and the dependent variable was medication compliance. Data collection was carried out using a family support questionnaire and a medical card observation sheet. Data analysis used the Chi-Square test with a significance level of α<0.05. The results showed that most respondents received good family support (32 respondents (88.9%) and the majority of respondents were compliant with taking medication (35 respondents (97.3%). The chi-square test yielded a p-value of 0.004 (<0.05), indicating a relationship between family support and medication adherence in pulmonary TB patients. The study concluded that family support significantly correlates with medication adherence in pulmonary TB patients. Emotional support was the most dominant form of support in improving medication adherence in pulmonary TB patients.